Termination of Prosecutions Based on Restorative Justice in The Settlements of Criminal Cases In The Area Of The Hight Prosecutors Of Lampung - Citizen, Yuris Oktaviyani (Pancasila and Law Review, 2022)
The Attorney General's Office of the Republic of Indonesia has introduced a significant initiative to resolve cases through the termination of prosecutions based on restorative justice. The Prosecutor's Office, functioning as a case controller under the dominus litis principle, plays a crucial role in the successful implementation of restorative justice in Indonesia. This article examines and analyzes the application and challenges of terminating prosecutions based on restorative justice within the Lampung High Court jurisdiction. Utilizing both normative juridical and empirical juridical research methods, this study draws on six sources, including academic literature and input from the Public Prosecutor at the Lampung High Prosecutor's Office. The data were processed and analyzed cumulatively. The findings indicate that the Lampung High Court has successfully implemented restorative justice-based prosecutions in three District Attorney's Offices. However, significant obstacles persist, including overlapping regulatory frameworks between law enforcement agencies, such as the Prosecutor's Office and the police, which contribute to legal uncertainty and inconsistencies in law enforcement, as well as insufficient community participation, particularly among victims.